Esensi Kemampuan Mengajar dalam Upaya Peningkatan Hasil Belajar Siswa - Nurdin Mansur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
A teacher who has a good and high qualifications as a subject teacher will be able to carry out the teaching and learning activities with the kind and quality as well. The above capabilities which can be seen when teachers plan lessons, implementing the learning, and when it conducted an assessment of student learning outcomes. Various teacher's ability to teach is meant, among others, is the ability of teachers in the mastery of the subject matter, the teacher's ability to manage the learning process, the ability of teachers to manage the classroom, the teacher's ability to use the media, the ability of teachers to use teaching methods, the teacher's ability to manage interactions learning, and the ability of teachers to assess student learning outcomes. If the above is owned by someone of teachers in teaching and learning activities, the students will enjoy learning with a teacher who has a good ability in conducting teaching and learning activities, so that by itself would be able to evoke the spirit of students to study in earnest. That the teaching and learning activities carried out teachers who have and are able to apply a wide range of capabilities to effectively and efficiently, it will make students like the subjects he teaches, so that students are trying to learn as well as possible the subject matter presented gurnya and eventually students will get the results of learning tall one.